Uprising the Pueblo Indians and the first American war for religious freedom - Page, Jake (Tucson, Arizona Rio Nuevo Publishers, 2013)
The Pueblo Revolt of 1680 changed the course of history. It was the only war that American Indians ever won against the Europeans. In this new nonfiction account, Jake Page delves into the events leading up to the revolt, its aftermath, and the less well-known second revolt.
Introduction -- Part One: Beginnings -- Part Two: Calamity -- Part Three: The Province Regained -- Part Four: Aftermath -- Endnotes -- Bibliography -- Acknowledgments -- Index
Includes Index and Bibliography
101101
Keywords: Pueblo Revolt -- 1680.; Pueblo Indians -- Wars; Pueblo Indians -- Religion